Tregalizumab – A Monoclonal Antibody to Target Regulatory T Cells - König, Martin; Rharbaoui, Faiza; Aigner, Silke; Dälken, Benjamin; Schüttrumpf, Jörg (Frontiers in Immunology, 2016)
Regulatory T cells (Tregs) represent a subpopulation of CD4+ T cells, which are essential for the maintenance of immunological tolerance. The absence or dysfunction of Tregs can lead to autoimmunity and allergies. The restoration of functional Tregs and/or Treg cell numbers represents a novel and attractive approach for the treatment of autoimmune diseases, e.g., rheumatoid arthritis (RA). The CD4 cell surface receptor is a target for modulation of T cell function. Monoclonal antibodies (mAbs) against CD4 have previously been tested for the treatment of autoimmune diseases, including RA. Furthermore, in model systems, anti-CD4 antibodies are able to induce tolerance and mediate immunomodulatory effects through a variety of mechanisms. Despite the availability of innovative and effective therapies for RA, many patients still have persistently active disease or experience adverse events that can limit use. A growing body of evidence suggests that Treg modulation could offer a new therapeutic strategy in RA and other autoimmune disorders. Here, we describe tregalizumab (BT-061), which is a novel, non-depleting IgG1 mAb that binds to a unique epitope of CD4. Tregalizumab represents the first humanized anti-CD4 mAb that selectively induces Treg activation.